Behind the lines revealing and uncensored letters from our war-torn world - Carroll, Andrew (Ebury Press, 2005)
In 2001, Andrew Carroll authored the US top ten bestseller, "War Letters" - a compilation of correspondence from American soldiers serving in US conflicts throughout history. Following the publication, he was inundated with letters from soldiers all around the world. This book is an anthology that has been put together as a result of this work.